The Harder You Work, the Higher Your Satisfaction With Life? The Influence of Police Work Engagement on Life Satisfaction: A Moderated Mediation Model - Liu, Ting; Zeng, Xiaoqing; Chen, Meirong; Lan, Ting (Frontiers in Psychology, 2019)
Background: Life satisfaction is a key component of quality of life; it is associated with many factors, including occupational and family life. The results of existing studies examining associations among work engagement, work-family conflict, and life satisfaction have been inconsistent. Objective: We explored the mechanism of action of police work engagement on life satisfaction, and analyzed the relationships among work engagement, work-family conflict, psychological detachment, and police life satisfaction from the angle of family and work relationships. Methods: A total of 760 police officers completed the Utrecht Work Engagement Scale, Satisfaction with Life Scale, Work-Family Conflict Scale, and Psychological Detachment Scale; 714 questionnaires were valid. Results: Work engagement both directly affected police life satisfaction (β = 0.58, p < 0.001), and indirectly influenced police life satisfaction through work-family conflict (β = -0.07, p < 0.05). Different levels of psychological detachment moderated both the relationship between work engagement and work-family conflict (β = 0.17, p < 0.001), and the relationship between work-family conflict and life satisfaction (β = 0.07, p < 0.05). Conclusion: A moderated mediation model was established. Work-family conflict partially mediates the relationship between work engagement and police life satisfaction. Psychological detachment moderates the first and second half of the mediating process by which work engagement affects police life satisfaction through work-family conflict.